Application of Balint groups activity to relieve anxiety among newly recruited nurses (巴林特小组活动缓解新入职护士焦虑情绪的应用研究) - ZHANG Aihui (张瑷珲); MA Jianying (马建映); YE Liping (叶丽萍) (中西医结合护理)
Objective To evaluate the application of Balint groups activity to relieve anxiety among newly recruited nurses. Methods Totally 38 newly recruited nurses were included as research objects. The Balint groups activity was carried out once per three months, and scores of Chinese Nurses Stressor Scale and Self-rating Anxiety Scale (SAS) before and after activity were compared. Results After implementation of Balint groups activity, dimension scores of work environment and resources, workload and time allocation, nursing profession and work increased significantly (P＜0. 05), and score of SAS dropped significantly compared with that before intervention (P＜0. 05). Conclusion The Balint groups activity is potentially effective to relieve anxiety and related employment pressure among newly recruited nurses. (目的 探讨巴林特小组活动在缓解新入职护士焦虑情绪中的应用效果。方法 将2018届新入职护士38名作为研究对象, 于2018年10月—2019年9月每季度组织1次巴林特小组活动。比较活动前后新入职护士中国护士工作压力源量表以及焦虑自评量表(SAS)评分。结果 巴林特小组活动实施后, 新入职护士在中国护士工作压力源量表中的工作环境及资源、工作量及时间分配、护理专业及工作维度的评分较活动前升高, SAS评分较活动前明显降低, 差异有统计学意义(P＜0. 05)。结论 巴林特小组活动能有效缓解新入职护士的焦虑情绪, 改善新入职护士的就业压力。)